Introduction of KPIs in the field of public service - Saidarifov, Kh.; Kairkenova, D.; Yermekov, Ch. (Maqsut Naribayev University International School of Economics, 2023)
The purpose of this study is to determine how well Key Performance Indicators (KPIs) work in assessing and enhancing the performance of UK public sector organizations. The study investigates the effectiveness of KPIs in the UK public sector, government regulations and recommendations related to KPI implementation, and discussions around the usage of KPIs through a thorough literature analysis. The results provide a complicated picture, with performance increases in different government agencies noted, but also difficulties and drawbacks including unintended repercussions and data manipulation. The research assesses the use of KPIs in the guidelines offered by the HM Treasury's Green Book, a crucial tool for policy review in the UK. Although the Green Book highlights the necessity of utilizing suitable performance measurements, such as KPIs, there have been complaints about its implementation and the requirement for ongoing development in order to handle new difficulties. In order to assess the effects of KPI implementation, the research also looks at departmental performance in specific government agencies, such as the Ministry of Defense (MOD), National Health Service (NHS) England, and Department for Business, Energy, and Industrial Strategy (BEIS). It has been noted that although some departments have achieved performance increases linked to the usage of KPIs, others struggle to create the proper KPIs and prevent unexpected repercussions. The results' implications emphasize the necessity of designing meaningful and pertinent KPIs, strong governance and data integrity procedures, and a culture of ongoing assessment and development. The paper also points up potential directions for further investigation, such as tools for spotting data manipulation in KPIs and in-depth departmental performance evaluation. Overall, this study sheds information on the efficacy, difficulties, and potential policy ramifications of KPIs in the UK public sector. It is a useful tool for researchers, practitioners in the public sector, and policymakers who want to improve performance monitoring and delivery of public services.
Keywords: KPIs in the UK public sector